Macro expectations, aggregate uncertainty, and expected term premia - Christian D. Dick; Maik Schmeling; Andreas Schrimpf (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
Based on individual expectations from the Survey of Professional Forecasters, we construct a real-time proxy for expected term premium changes on long-term bonds. We empirically investigate the relation of these bond term premium expectations with expectations about key macroeconomic variables as well as aggregate macroeconomic uncertainty at the level of individual forecasters. We find that expected term premia are (i) time-varying and reasonably persistent, (ii) strongly related to expectations about future output growth, and (iii) positively affected by uncertainty about future output growth and inflation rates. Expectations about real macroeconomic variables seem to matter more than expectations about nominal factors. Additional findings on term structure factors suggest that the level and slope factor capture information related to uncertainty about real and nominal macroeconomic prospects, and that curvature is related to subjective term premium expectations themselves. Finally, an aggregate measure of forecasters' term premium expectations has predictive power for bond excess returns over horizons of up to one year.
Keywords: E43; E44; G12; 330; Zinsstrukturtheorie; Zins; Risikoprämie; Finanzanalysten; Erwartungstheorie; Konjunktur; USA